2016
DOI: 10.22452/jummec.vol19no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Attendance and Institutional Facilities of Long-Term Kidney Donors Follow-Up

Abstract: Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In this study, it was found that UMMC incurred a huge nancial implication to manage COVID-19 alone. In fact, the amount is disproportionately large considering it is a single disease, compared to the other chronic diseases and malignancies treated at the centre [15,[18][19][20]. Should there be no reserved fund and nancial assistance from the institutions and personnel, the hospital budget at that time might be challenging to manage the pandemic on top of other non-COVID cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that UMMC incurred a huge nancial implication to manage COVID-19 alone. In fact, the amount is disproportionately large considering it is a single disease, compared to the other chronic diseases and malignancies treated at the centre [15,[18][19][20]. Should there be no reserved fund and nancial assistance from the institutions and personnel, the hospital budget at that time might be challenging to manage the pandemic on top of other non-COVID cases.…”
Section: Discussionmentioning
confidence: 99%